Effects of waterlogging on ion accumulation and sugar, protein and proline contents in Corchorus capsularis L. - Parvin, Dilruba; Karmoker, JL (Bangladesh Journal of Botany, 2013)
Waterlogging decreased accumulation of K+, Ca2+, Mg2+, NO3 - and PO4 3- but increased that of Na+ and Fe2+in the root, stem and leaves of jute (Corchorus capsularis L.). It increased the accumulation of sugar and proline contents but decreased that of protein as well as dry weight. The effect of waterlogging on ion transport, accumulation of metabolites and dry weight was discussed. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15864 Bangladesh J. Bot. 42(1): 55-63, 2013 (June)